Recurrent small bowel obstruction in a 30-year-old patient with Ladd’s syndrome - E. G. Grigoryev; V. M. Dehnich; E. O. Inozemtsev (Вестник хирургии имени И.И. Грекова)
We report the case of treatment of a 30-year-old woman with an impaired passage in the duodenojejunal segment of the gastrointestinal tract due to Ladd’s syndrome. Occlusion of the superior mesenteric artery was developed as a result of incomplete rotation of midgut in dysembryogenesis. Mesenteric blood circulation was compensated by collaterals formed in the antenatal period. Ladd’s operation was performed to treat acute intestinal failure, the duodenojejunal passage was restored. The patient was discharged on the 11th postoperative day in a good condition with the main diagnosis «Ladd’s syndrome». In the presented case report, the impaired passage in the gastrointestinal tract in the middle age patient was traced from childhood. Detailed examination of medical history, correct interpretation of MSCT findings allowed to form an accurate diagnosis and perform effective surgical treatment.